2017
DOI: 10.26477/idj.v39i2.125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Autoclave on Bacterial Growth Isolated from Different Types of Denture Adhesives

Abstract: Background: Different types of denture adhesives like powder or paste have been used to enhance the retention and stability in denture wearers, especially in patients with resorbed ridges , these adhesives should be free from microbial contamination in order to use safely inside patient mouth and avoid infection , the purpose of this study is to investigate the bacterial contamination of different adhesives pastes and powders and the effect of autoclaving in reducing the bacterial growth . Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Then all samples put in thermocycling (Julabo Labortechnix, GMBH, Germany) for subjecting to (5 ± 1 °C-55±1 °C, 500 cycles) for 60 seconds in an isolated container [28]. Then the autoclaved groups were exposed to the sterilization by autoclave (HICLAVE HV-25 L, HIRAYAMA, Japan) monitored as fellow: 121 °C temperature, 15 pound/inch 2 pressure, and 15 minutes as immersion time, the diameter and thickness of each specimen was rechecking by vernier to exclude any distorted specimen [19]. In addition, the non-autoclaved groups remained without autoclave disinfection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then all samples put in thermocycling (Julabo Labortechnix, GMBH, Germany) for subjecting to (5 ± 1 °C-55±1 °C, 500 cycles) for 60 seconds in an isolated container [28]. Then the autoclaved groups were exposed to the sterilization by autoclave (HICLAVE HV-25 L, HIRAYAMA, Japan) monitored as fellow: 121 °C temperature, 15 pound/inch 2 pressure, and 15 minutes as immersion time, the diameter and thickness of each specimen was rechecking by vernier to exclude any distorted specimen [19]. In addition, the non-autoclaved groups remained without autoclave disinfection.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the main interest of denture use is disinfection and controlling the contamination particularly in the prosthodontics branch [19]. Therefore, the indication of the autoclave as a sterilization method because of its good destroying of bacteria, fungi, viruses, and any reason that result in contamination of liquids and equipment in use [20].But some studies were reported that the specimens were suffered from the internal stress formation and shrinkage after heat postpolymerization, so to overcome this problem the specimens were left in the autoclaves for cooling to reduce shrinkage and internal stress formation [21,22].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%